Calculation x2 + 2x + 4 x2+4x+4÷x3−8 3x+6÷1 x2−4.

Calculation x2 + 2x + 4 x2+4x+4÷x3−8 3x+6÷1 x2−4.

Original formula = x2 + 2x + 4
(x+2)2÷(x−2)(x2+2x+4)
3(x+2)÷1
(x+2)(x−2)
=x2+2x+4
(x+2)2•3(x+2)
(x−2)(x2+2x+4)•(x+2)(x-2)
=3.

There is such a question: "calculate the value of (square of X - 2x + 1) / (square of X - 1) ÷ (x-1) / (square of X + x) - X There is such a question: "calculate the value of (x square - 2x + 1) / (x square - 1) ÷ (x-1) / (x square + x) - x, where x = 2010." classmate a miscopied "x = 2010" into "x = 2001", but his calculation result is also correct. What do you think is going on?

Because the value of (x squared - 2x + 1) / (x squared - 1) ÷ (x-1) / (x squared + x) - x is independent of X:
(square of X - 2x + 1) / (square of X - 1) ÷ (x-1) / (square of X + x) - x
=(x-1)^2/[(x+1)(x-1)] * x(x+1)/(x-1) -x
=x -x
=0

Calculate 2x squared + 8x + 8 / X squared + 2x + 1 divided by (x + 1) multiplied by X + 1 / x + 2

Square of 2x + 8x + square of X in 8 + 2x + 1 divided by (x + 1) multiplied by X + 1 x + 2 = (x ^ 2 + 2x + 1) / (2x ^ 2 + 8x + 8) * 1 / (x + 1) * (x + 2) / (x + 1) = (x + 1) ^ 2 / 2 (x ^ 2 + 4x + 4) * (x + 2) / (x + 1) ^ 2 = (x + 1) ^ 2 / 2 (x + 2) ^ 2 * (x + 2) / (x + 1) ^ 2 = 1 / 2 (x + 2)

(0.8,0.2) = 5 (3,5) = 1.6 (1 / 2,1 / 3) = 5 / 2 calculation (x, 1 / 2) Find the law and find the value of X

I don't know the value of (x, 1 / 2). I can't find the value of X. you should have missed it
The rule of this question is that the sum of the two numbers in parentheses divided by the second number = the value outside parentheses
(0.8,0.2)=(0.8+0.2)÷0.2=5
(3,5)=(3+5)÷5=1.6
(1/2,1/3)=(1/2+1/3)÷1/3=5/2
Therefore, if we know the value of (x, 1 / 2), we can use this law to find the value of X

Find out the law first, and then find the value of X. (0.8,0.2), (3,5) = 1.6, (1 / 2,1 / 3) = 5 / 2. Calculate: (x, 1 / 5) = 4

(x,1/5)=4
(x+1/5)/(1/5)=4
x+1/5=4/5
x=3/5

Calculate the square of X-5 / 1-x - 6-10 / 25 + 2x / x + 1

=1/(x-5)-6/(x+5)(x-5)-(x+1)/2(x+5)=2(x+5)/2(x+5)(x-5)-12/2(x+5)(x-5)-(x+1)(x-5)/2(x+5)(x-5)=(2x+10-12-x ²+ 4x+5)/2(x ²- 25)=(-x ²+ 6x+3)/(2x ²- 50)=-(x ²- 6x-3)/(2x ²- 50)